2022
DOI: 10.1007/s10459-022-10116-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different mindfulness interventions among health care students in Finland: a randomised controlled trial

Abstract: We investigated the short- and long-term effects of two different evidence-based mindfulness training on students’ stress and well-being. A randomised controlled trial with three measurement points (baseline, post-intervention, and 4 months post-intervention) was conducted among undergraduate students of medicine, dentistry, psychology, and logopaedics at the University of Helsinki. The participants were randomly assigned into three groups: (1) face-to-face mindfulness training based on the Mindfulness Skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Another major limitation in the field of online MBIs is the lack of high-quality randomized controlled trials demonstrating that online and traditional MBIs equally and positively affect mental health. While research in this area is still in its early stages, a few comparative studies have suggested that online MBIs may be equally effective [97][98][99]. Notably, these studies compared traditional MBIs with online interventions delivered by videoconferencing [97] or through web-based programs that included interaction with a teacher [98,99].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another major limitation in the field of online MBIs is the lack of high-quality randomized controlled trials demonstrating that online and traditional MBIs equally and positively affect mental health. While research in this area is still in its early stages, a few comparative studies have suggested that online MBIs may be equally effective [97][98][99]. Notably, these studies compared traditional MBIs with online interventions delivered by videoconferencing [97] or through web-based programs that included interaction with a teacher [98,99].…”
Section: Future Directionsmentioning
confidence: 99%
“…While research in this area is still in its early stages, a few comparative studies have suggested that online MBIs may be equally effective [97][98][99]. Notably, these studies compared traditional MBIs with online interventions delivered by videoconferencing [97] or through web-based programs that included interaction with a teacher [98,99]. This implies that the role of a skilled mindfulness instructor is pivotal in determining the overall benefit of online MBIs.…”
Section: Future Directionsmentioning
confidence: 99%
“…Practicing mindfulness entails experiencing the present moment, rather than trying to change anything (Marchand, 2012;Hofmann and Gómez, 2017;Sun et al, 2021). This present-centered self-awareness skill can be further developed through regular exercises (Repo et al, 2022), eventually enabling the individual to release certain frustrationlike habitual reactions (Liu X. et al, 2021) such as anxiety. Mindfulness could also be considered as the composition of both self-regulation of attention and an orientation to the present moment, characterized by curiosity, receptivity, and openness (Hofmann and Gómez, 2017).…”
mentioning
confidence: 99%